If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s = 4s + -60 Reorder the terms: s = -60 + 4s Solving s = -60 + 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. s + -4s = -60 + 4s + -4s Combine like terms: s + -4s = -3s -3s = -60 + 4s + -4s Combine like terms: 4s + -4s = 0 -3s = -60 + 0 -3s = -60 Divide each side by '-3'. s = 20 Simplifying s = 20
| 9x-20=7x+16 | | 140=(2x-2)(2x+2) | | 6(5-5y)= | | t^3+t=4930 | | 2z/2= | | 11+x+24=19+x+22 | | 0.75(4x+8)=-3 | | 5k-15+j=3j-5 | | 3(2g+7m)= | | (x+x)-20x+100=0 | | 0.2r=-8 | | v+53=3v+21 | | 9=5.4*x | | 5y^2+7y-4=0 | | 12-4p=-4(-5p-3) | | (5x-15)=what | | 5y-2=3x+2 | | 4(-2f-6g)= | | 3x=2.52 | | 140=4x^2-4+4-16 | | x^1000=0.9 | | 3y=-x+0 | | 13w+16w-7+5=-5w+5-7 | | 4x^2-156=0 | | 8(-4k-4)=-5k-32 | | 3(3+2j)= | | 3z-35=5z-87 | | 5m-13=n+5 | | u=2u-74 | | x=7x+6y | | 3q-70=q+26 | | (x+3)*5-5=20 |